Diectic Feet: performance as the index of animation - Vermy, Hans (Mimesis Journal, 2024)
The article investigates recent promotional campaigns launched by Hollywood to generate a sense of believability, identification, and connection between audiences and digitally animated characters, exploring why and how theatricality is summoned to lend respectability to the cartoon. The concept, technology, and branding of motion-capture is interrogated through aesthetic and theoretical instances of the step and walking, footprints and strides, and entrances and exits to reveal a theatrical historiography both rooted and reborn in a digital animation practice.